Analisis Ujaran Kebencian di Media Sosial Terhadap Denise Chairesta Dalam Kajian Linguistik Forensik (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
Social media has provided space for freedom of opinion to all its users. However, this has caused not only positive impacts but also negative impacts. This research aims to describe hate speech made by haters or someone who hates Denise Chairesta. The data source for this research was taken from the social media comments column on Instagram, Tiktok and Denise Chairesta's personal YouTube. The research method used is a descriptive method and uses a qualitative approach. The data collection techniques used in the research are documentation techniques and observation techniques with data analysis techniques which consist of three stages, namely data reduction, data presentation and conclusion. The results of the research found eight pieces of data that led to hate speech towards Denise Chairesta.